PEMBELAJARAN LAGU DAERAH GORONTALO “TIDI LO POLOPALO MELALUI STRATEGI ACTIVE LEARNING PADA SISWA KELAS VIII-B SMP - Arika Polamolo; Rahmawati Ohi; Mimy Astuty Pulukadang (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2026)
Music education, particularly the teaching of regional songs, plays an important role in fostering cultural appreciation and developing students’ musical skills. However, in practice, the learning of regional songs at SMP Negeri 3 Bone still faces various challenges, such as low student interest and learning motivation, as well as limited mastery of vocal techniques, including intonation, articulation, and breathing. This study aims to describe the learning process of the Gorontalo regional song Tidi Lo Polopalo through the implementation of an active learning strategy and to determine the effectiveness of this strategy in improving the vocal abilities of eighth-grade students (Class VIII-B) at SMP Negeri 3 Bone. This research employs a qualitative approach with a descriptive research design. Data collection techniques include observation, interviews, and documentation. The results indicate that the application of the active learning strategy increases students’ participation in the learning process, creates a more interactive and enjoyable learning atmosphere, and enhances students’ vocal abilities in terms of intonation, articulation, and breathing. Furthermore, learning regional songs through this strategy fosters students’ self-confidence, cooperation, and appreciation of Gorontalo local culture. Therefore, the active learning strategy is considered effective for use in teaching the regional song Tidi Lo Polopalo in the Cultural Arts subject at SMP Negeri 3 Bone. ABSTRAK Pembelajaran seni musik, khususnya pembelajaran lagu daerah, memiliki peran penting dalam menumbuhkan apresiasi budaya dan mengembangkan keterampilan musikal peserta didik. Namun, pada praktiknya pembelajaran lagu daerah di SMP Negeri 3 Bone masih menghadapi berbagai kendala, seperti rendahnya minat dan motivasi belajar siswa serta kurangnya penguasaan teknik vokal, meliputi intonasi, artikulasi, dan pernapasan. Penelitian ini bertujuan untuk mendeskripsikan proses pembelajaran lagu daerah Gorontalo Tidi Lo Polopalo melalui penerapan strategi active learning serta mengetahui efektivitas strategi tersebut dalam meningkatkan kemampuan vokal siswa kelas VIII-B di SMP Negeri 3 Bone. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian deskriptif. Teknik pengumpulan data meliputi observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa penerapan strategi active learning mampu meningkatkan keaktifan siswa dalam proses pembelajaran, menciptakan suasana belajar yang lebih interaktif dan menyenangkan, serta meningkatkan kemampuan vokal siswa dalam aspek intonasi, artikulasi, dan pernapasan. Selain itu, pembelajaran lagu daerah melalui strategi ini juga menumbuhkan rasa percaya diri, kerja sama, dan apresiasi siswa terhadap budaya lokal Gorontalo. Dengan demikian, strategi active learning dinilai efektif untuk diterapkan dalam pembelajaran lagu daerah Tidi Lo Polopalo pada mata pelajaran Seni Budaya di SMP Negeri 3 Bone.